BRS 328 - Double haploid bread wheat cultivar - Scheeren,Pedro Luiz (2014)
The wheat cultivar 'BRS 328' was developed by Embrapa from a cross between KleinH3394 and PF 990744. The pre-harvest sprouting resistance of 'BRS 328' is good and the grain yield high. It is classified as bread wheat cultivar in all regions where it is recommended for cultivation.